A New Monohydrogen Phosphate-Selective Carbon Composite Membrane Electrode for Soil Water Samples - Tavukcuoglu, Ozlem; Erci, Vildan; Ciftci, Fatih; Isildak, Ibrahim; Kasapoglu, Muhammed Zahid (MDPI, 2025)
This study focused on developing a novel composite phosphate-selective electrode for on-site and real-time applications using a silver polyglutaraldehyde phosphate and carbon nanotube (CNT) matrix. CNT-silver polyglutaraldehyde phosphate compound was synthesized and characterized using Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). The potentiometric performance of the composite phosphate-selective electrode was then investigated. The results demonstrated that the composite phosphate-selective electrode exhibited good sensitivity, with a linear response in the concentration range of 1.0 x 10-4 to 1.0 x 10-2 M for phosphate ions. The electrode also showed high selectivity towards phosphate ions compared to other anions, such as chloride and nitrate. Additionally, the electrode displayed a quick response time of less than 15 s, making it suitable for real-time measurements. The electrode was applied to surface and soil water samples. The results obtained from the water samples showed a strong correlation with those obtained from the preferred spectrophotometry method, highlighting the potential of the developed electrode for on-site and continuous monitoring of phosphate and offering an efficient and practical solution for various fields that require phosphate detection.
Keywords: composite matrix; phosphate-selective electrode; solid contact; soil analysis; PYRUVATE OXIDASE; BIOSENSOR; SENSOR; Materials Science